2014
DOI: 10.2139/ssrn.2580601
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Foreign Bank Lending Behavior During the 2008-2009 Crisis

Abstract: This paper analyzes the lending behavior of foreign-owned banks during the recent global crisis. Using bank-level panel data for 51 countries, the paper explores the role of affiliate and parent financial characteristics, host location, as well as the impact of parent geographic origin and reach on foreign banks' credit growth. Overall, the analysis finds robust evidence that foreign banks curtailed the growth of credit relative to other banks, independent of the host region in which they operate. Banks from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 24 publications
2
28
2
Order By: Relevance
“…This means the crisis has no significant impact on lending. The results are different from previous studies that found significant negative impacts of the crisis on lending (Silalahi, Wibowo, & Nurlian, 2012;Allen, Jackowicz, & Kowalewski, 2013;Choi, 2013;De Haas & Van Lelyveld, 2014). These results indicate the overall banking industry in Indonesia during the global economic crisis that occurred in 2008-2009 did not affect the decline in bank lending in Indonesia.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This means the crisis has no significant impact on lending. The results are different from previous studies that found significant negative impacts of the crisis on lending (Silalahi, Wibowo, & Nurlian, 2012;Allen, Jackowicz, & Kowalewski, 2013;Choi, 2013;De Haas & Van Lelyveld, 2014). These results indicate the overall banking industry in Indonesia during the global economic crisis that occurred in 2008-2009 did not affect the decline in bank lending in Indonesia.…”
Section: Discussioncontrasting
confidence: 99%
“…Allen, Jackowicz, & Kowalewski (2013) investigated the impact of the global economic crisis on lending of foreign banks and state-owned banks in the European region. While Choi (2013) examines the impact of the global crisis on lending in Europe, West Asia, and Latin America. This study complements these 3 studies in particular to examine the impact of the global economic crisis of 2008 and 2009 on lending foreign banks, joint ventures bank, domestic banks, and state-owned banks during 2002-2015 in Indonesia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerns about a dramatic credit crunch in the Central and Eastern European countries led to a concerted effort by regulators and multilateral institutions to preserve minimum levels of lending (De Haas et al, 2015). The crisis triggered an increasing research effort to disentangle the factors that drove the fall of credit growth in most countries from this region (see e.g., Choi et al, 2013;Feyen et al, 2014). In this section, we explore the role of risk management and corporate governance on banks' credit activity during the crisis.…”
Section: Credit Activity and Credit Losses During The Crisismentioning
confidence: 99%